FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA PERIODE TAHUN 2009-2011 (Students' Journal of Accounting and Banking, 2013)
This study aimed to obtain empirical evidence whether the size of the company, the company's profitability, solvency, quality auditor, and the auditor's opinion on the effect on the issuer's audit delay in IDX. The population in this study are all companies listed on the Indonesia Stock Exchange in 2009- 2011 observations. The samples in this study using purposive sampling method of sample selection was not random that the information obtained by certain considerations. Analysis using multiple linear regression analysis.The results showed that the size of the company's positive impact on audit delay, meaning that the higher the size of the company, then the company's audit delay is getting longer. Audit opinion and no significant positive effect on audit delay. Auditor reputation negatively affect audit delay, meaning the better the quality of the auditor, it will have a shorter delay time audt. Solvency positive effect on audit delay, meaning that the higher the solvency, the company's audit delay is getting longer. Profitability negatively affect audit delay, meaning that the higher profitability, it will have a shorter delay time auditKeywords: company size, profitability, solvency, quality auditor, and the auditor's opinion affect audit delay